Implementación de un Sistema de Información Web para mejorar la gestión de proyectos siguiendo los lineamientos de la Guía de los Fundamentos para la Dirección de Proyectos (Guía del PMBOK®) para la empresa SIGCOMT S.A.C - Argomedo De La Cruz, Richard Alexis (2017)
The present work of Thesis entitled "Implementation of a Web Information System to improve the management of projects following the guidelines of the Guide of the Fundamentals for Project Management (PMBOK® Guide) for the company SIGCOMT SAC" has been developed with the purpose of improving the management of projects aligned to the PMBOK Guide, through the development and implementation of a Web Information System, achieving the projects for better management, development and execution in the duration of the project; achieving also greatly reduce generation times and consult reports. For the development of the present study, the survey, the survey and the observation as the technique of data collection have been used, asking open and closed questions to the different interviewees, which served as a source of information to determine the scope of the project. We analyze the different results of the techniques mentioned above and serve to design and implement the web information system that develops this thesis. As a result of this research, it can be concluded that through the implementation of a Web Information System it is possible to improve project management following the PMBOK guidelines, besides the economic, operational benefits, the company image and others.